The dual anti-inflammatory and anticoagulant effects of Jianpi Huashi Tongluo prescription on Rheumatoid Arthritis through inhibiting the activation of the PI3K/AKT signaling pathway - Wang, Fanfan; Liu, Jian (Frontiers in Pharmacology, 2025)
BackgroundRheumatoid arthritis (RA) is often accompanied by abnormal changes in inflammatory responses and coagulation-fibrinolysis indicators. Jianpi Huashi Tongluo Prescription - Xinfeng Capsule (XFC), a traditional Chinese medicine formulation comprising multiple herbal ingredients, is widely used clinically for the treatment of RA. It exhibits dual anti-inflammatory and anticoagulant effects. However, the specific mechanisms underlying its actions remain to be further investigated.ObjectiveThis study aims to elucidate the anti-inflammatory and anticoagulant mechanisms of XFC in the treatment of RA.MethodsA multidimensional methodological framework was employed. Firstly, through retrospective clinical data mining, combined with the Apriori algorithm and random walk models, an in-depth analysis was conducted to explore the potential associations between XFC treatment and improvements in clinical inflammatory and coagulation markers among RA patients. Secondly, an adjuvant-induced arthritis rat model was established to directly observe the anti-inflammatory and anticoagulant effects of XFC in vivo. Furthermore, bioinformatics and network pharmacology techniques were applied to decipher the major active components and their targets of XFC. Lastly, a co-culture system of RA patient-derived peripheral blood mononuclear cells (RA-PBMCs) and vascular endothelial cells (VECs) was established to mimic the in vivo microenvironment, and the anti-inflammatory and anticoagulant mechanisms of XFC were validated in vitro.ResultsData mining analysis revealed abnormally elevated levels of inflammatory and coagulation markers such as fibrinogen (FBG), erythrocyte sedimentation rate (ESR), high-sensitivity C-reactive protein (Hs-CRP), and rheumatoid factor (RF) in RA patients (p < 0.001), and emphasized the close correlation between XFC treatment and the improvement of these markers including Hs-CRP, ESR, and RF (confidence >60% and lift >1). Animal experimental data indicated that XFC effectively reduced the levels of inflammatory and coagulant markers (IL-6, D-D, FBG, PAF, VEGF, and TF) in adjuvant-induced arthritis (AA) rats while enhancing the expression of anti-inflammatory factors (IL-10) (p < 0.05). Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) results suggested that the pharmacodynamic mechanism of XFC may be closely related to the regulation of the PI3K/AKT signaling pathway. Additionally, network pharmacology and molecular docking results show that the main active components of XFC, namely, calycosin-7-O-beta-D-glucoside, calycosin, and formononetin, exhibit excellent docking with the core targets HIF1A, PTGS2, and MMP9. In vitro co-culture model showed that XFC inhibited RA-related inflammatory responses and hypercoagulable states by suppressing the activation of the PI3K/AKT signaling pathway.ConclusionThis study demonstrates that XFC exerts its dual anti-inflammatory and anticoagulant effects, at least in part, by inhibiting the activation of the PI3K/AKT signaling pathway, providing potential insights into targeted therapy for RA.